Adrenaline May Contribute to Prothrombotic Condition via Augmentation of Platelet Procoagulant Response, Enhancement of Fibrin Formation, and Attenuation of Fibrinolysis - Golaszewska, Agata; Misztal, Tomasz; Marcinczyk, Natalia; Chabielska, Ewa; Rusak, Tomasz (Frontiers in Physiology, 2021)
Background Adrenaline is believed to play a role in thrombosis and hemostasis. The complex effect of its clinically relevant concentrations on thrombus formation, coagulation and fibrinolysis in human blood has never been specifically studied. Methods Confocal microscopy was used to study thrombus formation under flow, exposure of phosphatidylserine (PS) in adhered platelets, to evaluate clots density, and to measure kinetics of fibrin formation and external fibrinolysis under flow. Flow cytometry was utilized to assess PS exposure in non-adhered platelets. Kinetics of clot formation and internal fibrinolysis was evaluated by thromboelastometry. Platelet aggregation was measured by optical aggremometry. Kinetics of clot retraction was assessed by using digital camera. Results We found that adrenaline (1-10 nM) may enhance platelet activation evoked by subthreshold collagen (150 ng/ml), resulting in augmentation of platelet aggregation, thrombus formation under arterial flow conditions, platelet PS exposure, and formation of platelet-fibrin clots. Adrenaline-evoked augmentation of platelet adhesion and PS exposure was stronger at shear rate of 1600 s-1 than 1000 s-1 suggesting shear-dependent context of adrenaline action on platelets under flow. The development of platelet procoagulant response evoked by adrenaline+low collagen was associated with the formation of denser platelet-fibrin clots and the decrease in rate of internal and external fibrinolysis. The above phenomena were abolished by the α2-adrenergic receptor antagonist, rauwolscine. Adrenaline-collagen synergism, expressed as PS exposure, was significantly reduced by cyclooxygenase inhibitor (acetylsalicic acid), GPIIb/IIIa receptor blocker (tirofiban), and P2Y12 receptor antagonist (PSB 0739). Conclusions Clinically relevant concentrations of adrenaline may significantly augment responses of human platelets in the presence of subthreshold concentrations of collagen, which should be considered during therapies involving adrenaline infusion. Routinely used antiplatelet drugs may reduce the prothrombotic state evoked by adrenaline-collagen synergism.